Improvement in health-related quality of life with Botulinum toxin A injection in acquired superior oblique palsy - Chen, Chonglin; Xu, Meiping; Yu, Huanyun; Li, Yipao; Yu, Xinping (Frontiers in Medicine, 2023)
Purpose: To investigate the outcomes of Botulinum toxin A (BTA) injection into the inferior oblique (IO) muscle for management of unilateral acute acquired superior oblique paresis (SOP), and to evaluate health-related quality of life changes post-injection using the Adult Strabismus-20 (AS-20) questionnaire. Methods: A prospective cohort study of patients with unilateral acute acquired SOP who underwent BTA injection was performed. Four units of BTA were injected into the ipsilateral IO muscle. Ocular examinations were performed pre- and post-injection, including alignment, ocular movement, and cyclo-torsion deviation. The patients’ AS-20 questionnaire scores were analyzed. Result: Twenty-one patients with acute acquired SOP were included. The initial median vertical deviation was 5 PD (range 1–16), which was improved to 0 PD (range 0–10) at both one month and six months post-injection (P < 0.001and P<0.001, respectively). The median torsion deviation was 7 degrees (range 2–18) at baseline, and resolved to 0 degrees (range -3–5) at the one-month and 0 degrees (range -2–7) at the six-month follow-up (P < 0.001 and P<0.001, respectively). There were significant increases in the overall score (OASs), psychosocial subscale score (PSSs), and functional subscale score (FSSs) from the baseline values at both the one-month (P < 0.001, P < 0.001, and P = 0.001, respectively) and six-month follow-ups (all P < 0.001). Conclusion: Injecting BTA into the ipsilateral IO muscle successfully resolved vertical and torsion deviation, and significantly improved quality-of-life scores. Our findings show that BTA treatment, as an early management of acute acquired SOP, can help patients by significantly improving their quality of life.